Attacking Deterministic Signature Schemes Using Fault Attacks - Poddebniak, Damian; Somorovsky, Juraj; Schinzel, Sebastian; Lochter, Manfred; Rösler, Paul (Proceedings - 3rd IEEE European Symposium on Security and Privacy, EURO S and P 2018, 2018)
Many digital signature schemes rely on random numbers that are unique and non-predictable per signature. Failures of random number generators may have catastrophic effects such as compromising private signature keys. In recent years, many widely-used cryptographic technologies adopted deterministic signature schemes because they are presumed to be safer to implement. In this paper, we analyze the security of deterministic ECDSA and EdDSA signature schemes and show that the elimination of random number generators in these schemes enables new kinds of fault attacks. We formalize these attacks and introduce practical attack scenarios against EdDSA using the Rowhammer fault attack. EdDSA is used in many widely used protocols such as TLS, SSH, and IPSec, and we show that these protocols are not vulnerable to our attack. We formalize the necessary requirements of protocols using these deterministic signature schemes to be vulnerable, and discuss mitigation strategies and their effect on fault attacks against deterministic signature schemes.
CRIS-Team Scopus Importer:2022-11-14
Keywords: Deterministic; Ed25519; EdDSA; Fault attacks; Rowhammer; Signatures